Early selection induced by perceptual load in a patient with frontal lobe damage: External vs. internal modulation of processing control. - Kumada, T; Humphreys, G (2002)
We examined effects of interference from task-irrelevant information in a patient with frontal and temporal lobe damage (FK), using Simon and reverse-Simon tasks. FK responded to the meaning or location of a word (LEFT or RIGHT), while ignoring the irrelevant dimension. When the dimensions were incongruent, FK showed large interference effects. However, when noninformative distractors (e.g., XXXX) were presented as a perceptual load in the reverse-Simon task, the size of the interference effect reduced as a function of the number of distractors. RT-distribution analyses revealed that the reduction of interference was due to increased correct responses in the fast end of the distribution. Opposite effects occurred in the standard Simon task. These results are consistent with perceptual load leading to early visual selection (Lavie, 1995). The results suggest that FK has intact processing of the location and meaning of words, but there is impaired internal control of attentional resources to the task-relevant information. In contrast, resources can be controlled externally, by increasing the perceptual load. We discuss the implications for understanding attentional modulation of visual processing.